Lesional insular epilepsy mimicking treatment refractory trigeminal neuralgia effectively treated with epilepsy surgery: A case report - Demuni P Jayasena; Karunanayaka A S K Karunanayaka; Sudath Gunasekara; Pathberiyage L S Pathberiya; Sanjeewa Garusinghe; Amila Chandrakumara; Sunethra Senanayake; Inuka K Gooneratne (Cephalalgia Reports)
Background Ictal epileptic headache is a very rare form of painful seizure that closely mimics several classic headache syndromes, including trigeminal neuralgia. Case Here, we present a woman who was treated as for treatment-refractory unilateral trigeminal neuralgia over 10 years, which was later deemed to be due to somatosensory seizures from the insular cortex. A cavernous haemangioma in the right insular cortex was identified as the causative lesion for these recurrent seizures and was successfully treated with resective surgery. Conclusion This case underscores the importance of considering lesional ictal epileptic headaches as a differential diagnosis of treatment-resistant neuralgiform headaches, which can be effectively managed by targeted surgical resection thereby inducing long-term headache or seizure remission.